2021
DOI: 10.1002/jia2.25761
|View full text |Cite
|
Sign up to set email alerts
|

The HIV care cascade in sub‐Saharan Africa: systematic review of published criteria and definitions

Abstract: Introduction:The HIV care cascade examines the attrition of people living with HIV from diagnosis to the use of antiretroviral therapy (ART) and suppression of viral replication. We reviewed the literature from sub-Saharan Africa to assess the definitions used for the different steps in the HIV care cascade. Methods: We searched PubMed, Embase and CINAHL for articles published from January 2004 to December 2020. Longitudinal and cross-sectional studies were included if they reported on at least one step of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 108 publications
(474 reference statements)
0
19
0
Order By: Relevance
“…When a fixed-denominator is used, there is internal consistency, and the continuum of care across the cascade relates to the single most important denominator, women in care [14]. In contrast, when a changing-denominator is used [1,9,13], problems with retention (retention gaps) at different stages of the cascade are highlighted [20,21]. We used guideline-indicated time-frames in these analyses (S1 Table ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When a fixed-denominator is used, there is internal consistency, and the continuum of care across the cascade relates to the single most important denominator, women in care [14]. In contrast, when a changing-denominator is used [1,9,13], problems with retention (retention gaps) at different stages of the cascade are highlighted [20,21]. We used guideline-indicated time-frames in these analyses (S1 Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Cervical cancer incidence and mortality decrease when screening programs engage and retain women from screening to treatment to follow-up along a care continuum [9,10]. The HIV care cascade has been successfully used to scale-up of antiretroviral therapy (ART) [11][12][13][14][15]. We believe the cascade approach could be similarly used to scale-up cervical cancer screening, supporing the WHO goal to eliminate cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…There appeared to be a stronger focus on HIV prevention compared to the HIV care and treatment components in the HIV prevention, care, and treatment continuum of care. In contrast, a recent all age-inclusive systematic review of the HIV care cascade in SSA found that viral suppression was the most frequently studied component, followed by diagnosis and linkage to care [61]. This systematic review also included articles from as far back as 2004 and was not limited to implementation science studies, which may, along with the all age-inclusive focus, account for the contrasting findings.…”
Section: Implementation Science Characteristicsmentioning
confidence: 98%
“…A recent systematic review of published criteria and definitions across the HIV care cascade in sub-Saharan Africa found that proportions of individuals retained in care at each step of the HIV care cascade cannot be compared between studies due to the highly variable definitions used for numerators and denominators; this review concluding that there is a need for standardized methods and definitions [ 29 ]. In general, the review process of reengagement also revealed an urgent need to standardize conceptualization and representation of the reengagement cascade and how to harmonize quantification of effects.…”
Section: Tracing and Reengagement In Carementioning
confidence: 99%